Lost Wages Secondary to Ankle Arthritis in Patients Undergoing Ankle Fusion or Replacement. Issue 3 (11th September 2017) - Younger, Alastair; Wing, Kevin; Veljkovic, Andrea; Penner, Murray; Gagné, Oliver
Category: Ankle Arthritis Introduction/Purpose: Wait lists for consultation and surgery for ankle arthritis are often over three years in our Province. While waiting for surgery patients may become unemployed and lose income. Earlier consultation and earlier treatment may allow these patients to return to work. The purpose of this paper is to calculate the lost wages annually and over the remaining working lifetime of a cohort of patients, and use this to extrapolate the lost wages for patients undergoing ankle arthritis surgery in the Province of British Columbia. Methods: Using data from an ankle outcome database, patients under the age of 60 were studied. Employment was recorded at the time of surgery, at 2 years, and an average 6.7 years follow up. Using the MODEMS instrument, patients self classified as (1) working, (2) on leave of absence, (3) unemployed, (4) homemaker, (5) student, (6) Retired (not due to ill health), (7) disabled or retired due to ill health. Items 2, 3, 7 were considered unemployed and items 1, 4, 5, 6 employed. Using annual rates of ankle arthritis surgery from our Province of 4.6 million people, the cumulative lost income was determined using the statistics Canada website (http://www12.statcan.gc.ca/nhs-enm/2011). Lost wages were calculated from the time of surgery until 75. All figures are quoted in Canadian dollars. Results: 127 of 276 database patients (46%) were under the age of 60 at the time of surgery. The average age was 51 years. 61 (48%) were unemployed. 2 years after surgery the unemployment rate was 42% and remained a similar rate at mean 6.7 years after surgery. There were 140 ankle arthritis operations in 2013 in our Province. Using the database rates the lost wages the working lifetime of these patients is $ 22.8 million. Using prior statistics (FAI 2015) the total surgical cost of ankle arthritis surgery in the Province is $ 1.1 million (1/20th the lost income). The cumulative lost wages per million population per year for ankle arthritis is 4.9 million dollars, and the money spent on surgery is 0.24 million dollars. Conclusion: The lost wages within the ankle arthritis population is of concern with regards to productivity, as well as the mental health and financial stability of these patients and their families. Earlier access to care may maintain the employment status in this patient group. Once patients are out of the work force it is very hard for them to return. The money spent on surgery is 1/20th of the lost wages.